An Text Study and Appreciation of Imam Ibn Katsir's Work: Kitab Al Bidayah Wa An Nihayah - Basor, Saepul; Sugiarto, Deri; Hakim, Ajid; Putra, M Zikril Oksa (Studi Multidisipliner: Jurnal Kajian Keislaman, 2024)
Al-Bidayah wa An-Nihayah is one of Ibn Kathir's monumental works covering the history of mankind from the creation of Adam to his time. This book is an encyclopedia of Islamic history written in an interesting and detailed writing style. In the study of the text of this book, several interesting things can be found, including: Ibn Kathir's critical and objective writing methodology in presenting historical events. He tried to avoid the element of subjectivity by referring to credible primary sources. The breadth of the scope of the discussion is not only limited to the history of Islam, but also includes the history of previous peoples such as the Prophets, the Romans, Persians, and others. Ibn Kathir's in-depth analysis of various historical events and their contextualization with the situation of his time. Ibn Kathir's writing style is communicative so that it is easily understood by the reader. The study of the text of this book can provide a comprehensive understanding of the history of mankind, especially from an Islamic perspective. In addition, this book can also be used as an important reference for the study of Islamic history.